2017
DOI: 10.1155/2017/7561909
|View full text |Cite
|
Sign up to set email alerts
|

Application of Genomic In Situ Hybridization in Horticultural Science

Abstract: Molecular cytogenetic techniques, such as in situ hybridization methods, are admirable tools to analyze the genomic structure and function, chromosome constituents, recombination patterns, alien gene introgression, genome evolution, aneuploidy, and polyploidy and also genome constitution visualization and chromosome discrimination from different genomes in allopolyploids of various horticultural crops. Using GISH advancement as multicolor detection is a significant approach to analyze the small and numerous ch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
21
0
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 30 publications
(22 citation statements)
references
References 58 publications
0
21
0
1
Order By: Relevance
“…In situ hybridization, using the genomic DNA of one or two species as a probe, is an effective way of identifying chromosomes from different sources in interspecific hybrids (Ramzan et al 2017). It has often been used for characterizing somatic hybrids, especially from the families Brassicaceae (Tu et al 2008;Du et al 2009), Poaceae (Cai et al 2007), Solanaceae (Escalante et al 1998;Kulawiec et al 2003), or Amaryllidaceae (Buiteveld et al 1998b;Yamashita et al 2002).…”
Section: Cytogenetic Description Of Somatic Hybridsmentioning
confidence: 99%
“…In situ hybridization, using the genomic DNA of one or two species as a probe, is an effective way of identifying chromosomes from different sources in interspecific hybrids (Ramzan et al 2017). It has often been used for characterizing somatic hybrids, especially from the families Brassicaceae (Tu et al 2008;Du et al 2009), Poaceae (Cai et al 2007), Solanaceae (Escalante et al 1998;Kulawiec et al 2003), or Amaryllidaceae (Buiteveld et al 1998b;Yamashita et al 2002).…”
Section: Cytogenetic Description Of Somatic Hybridsmentioning
confidence: 99%
“…Intergenomic recombination chromosomes containing chromosome segments from both parental species can be readily identified, and their behaviour and transmission can be monitored through meiosis into the progenies as shown in Lilium interspecific hybrids and Elymus dahuricus (Kwon et al, 2017;Yang et al, 2017). Ramzan et al (2017) has recently reviewed the application of GISH in horticultural plants and concluded that GISH has been used to perform chromosomal evaluation, cytogenetical classification, genomic constitution, polyploidy confirmation, hybrid verification and introgression breeding. In this study, the OxG hybrids were backcrossed using E. guineensis (tenera) as male parent for developing (GISH) method.…”
Section: Short Communication: Genomic Constitution Of Oil Palm Intersmentioning
confidence: 99%
“…GISH analyses may facilitate the choice of promising hybrids during the early stages of breeding through the detection of alien chromatin. This characterization allows the planning of crosses, aiming to maximize the segregation for the recovery of superior genotypes (Fukuhara et al, 2016;Liu et al, 2017;Ramzan et al, 2017;Grewal et al, 2018;).…”
Section: Introductionmentioning
confidence: 99%